2021
DOI: 10.12659/aot.934738
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Developing BK Virus-Associated Nephropathy: A Single-Center Retrospective Cohort Study of Kidney Transplant Recipients

Abstract: Background BK virus (BKV) infection after kidney transplantation leads to BKV-associated nephropathy (BKVAN) in up to 10% of recipients, and is associated with an increased risk of allograft dysfunction or loss. The objective of this study was to estimate the incidence of BKVAN and to analyze whether enhanced induction is associated with an increased risk of BKVAN, possibly justifying more intensive surveillance. Material/Methods This was a single-center retrospective c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 36 publications
2
8
0
Order By: Relevance
“…Radtke et al 24 found that neither induction nor maintenance immunosuppressive therapy influenced BKV infection. The same results were recently found by Lorant et al 25 Authors studied 44 patients with biopsy-proven PVAN and found that enhanced induction (including thymoglobulin), was not associated with BKV PVAN development after KT. We postulated that the use of modern low-dose concepts of immunosuppression in KT, merely impacts polyomavirus replication after KT.…”
Section: Discussionsupporting
confidence: 86%
“…Radtke et al 24 found that neither induction nor maintenance immunosuppressive therapy influenced BKV infection. The same results were recently found by Lorant et al 25 Authors studied 44 patients with biopsy-proven PVAN and found that enhanced induction (including thymoglobulin), was not associated with BKV PVAN development after KT. We postulated that the use of modern low-dose concepts of immunosuppression in KT, merely impacts polyomavirus replication after KT.…”
Section: Discussionsupporting
confidence: 86%
“…Finally, in a multivariable analysis, we confirmed the previously reported and widely recognized association between male age, acute rejection episodes, and the onset of PyVAN [33][34][35][36]. The present study has some limitations, mainly concerning the limited sample size, the lack of information about the expression of KIRs, the lack of analyses on NK cells subsets expressing the KIRs most relevant for PyVAN development and matched-pair randomized groups of recipients.…”
Section: Trydzenskaya Et Al Was the First To Define A Role For Kirs I...supporting
confidence: 81%
“…Indeed, when the immune system is suppressed (as in RTRs and in transplanted individuals in general), the virus may reactivate and, as a consequence of its replication, trigger a series of effects that begin with tubular cell lysis and the excretion of BKV in urine. Thereafter, BKV replicates in the interstitial cells and crosses the peritubular endothelial barrier, reaching the bloodstream and eventually the allograft, causing different tubular and interstitial damages with consequent serious complications, such as BKVN [ 15 ]. BKVN can induce the degeneration of transplanted kidney and graft failure [ 16 ], and patient outcome is determined by the severity of injury with consequent inflammatory and fibrosis pictures.…”
Section: Bk Virusmentioning
confidence: 99%
“…It was reported recently in a single-center retrospective study the effects of the so-called enhanced induction, (based upon the administration of thymoglobulin, rituximab, and/or eculizumab), together with age, sex, cytomegalovirus mismatch (donor +/recipient−) and transplant failure treatment as risk factors for developing BKVN. Results show that male gender, but not enhanced induction, represents a hazard for developing BKVN [ 15 ]. Moreover, in another very recent research work has been assessed the relationship between laboratory data and a higher risk of BKV activation.…”
Section: Bkv Nephropathymentioning
confidence: 99%